Open-Label Placebo Administration Decreases Pain in Elderly Patients With Symptomatic Knee Osteoarthritis – A Randomized Controlled Trial - Olliges, Elisabeth; Stroppe, Sabine; Haile, Anja; Reiß, Fabienne; Malhis, Marwa; Funke, Susanne A.; Meissner, Karin (Frontiers in Psychiatry, 2022)
Background Recent studies indicate that the administration of open-label placebos (OLP) can improve symptoms in various medical conditions. The primary aim of this 3-week randomized controlled trial was to examine the effects of OLP treatments on pain, functional disability, and mobility in patients with arthritic knee pain. Methods Sixty patients (55% females; mean age, 66.9 ± 9.7 SD years) were randomized to one of two OLP treatments (n = 41) or no treatment (NT; n = 19). OLP treatments were accompanied by the verbal suggestion “to decrease pain” (OLP-pain, n = 20) or “to improve mood” (OLP-mood, n = 21). Pain and mood levels were monitored on 11-point Numeric Rating Scales (NRSs) in a patient diary, and global clinical improvement (CGI-I) was assessed at the end of the study. At baseline and after 21 days, patients filled in validated questionnaires to assess symptoms and functional disability of the knee (WOMAC), mental and physical quality of life (SF-36), state anxiety (STAI-state), perceived stress (PSQ-20), and self-efficacy (GSE). In addition, knee mobility (neutral zero-method), heart rate variability (HRV), and diurnal cortisol levels were evaluated before and after treatment. Results Evaluation of daily pain ratings indicated significant pain decrease in the OLP groups compared to NT (p = 0.013, d = 0.64), with no difference between the OLP-pain and the OLP-mood groups (p = 0.856, d = 0.05). OLP treatment also improved WOMAC pain (p = 0.036, d = 0.55), again with no difference between the two OLP groups (p = 0.65, d = 0.17). WOMAC function and stiffness, knee mobility, stress, state anxiety, quality of life, and self-efficacy did not change differently between groups. Conclusion OLP treatment improved knee pain in elderly patients with symptomatic knee osteoarthritis (OA), while functional disability and mobility of the knee did not change. The content of the verbal suggestion was of minor importance. OLP administration may be considered as supportive analgesic treatment in elderly patients with symptomatic knee OA. Trial Registration German Clinical Trials Register (https://www.drks.de/), DRKS00015191 (retrospectively registered).